(3JMQjQ GdaJGhi Ydi GdJfHjg hGdefgGL hGdMGhjs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s ((3CMeO Hf eMeO Hf Ydi GdfGSN s)
(3ChdgG (B:s
(3MeOG ddg Ydi GdJfHjg Ydi GdefgGL hGdUdGI hGdSdGe Ydi GdfHi GdYQHi hGdBd hGdCUMGH hGdCRhGL agPG JYdjb Ydi GdJfHjg hGdefgGL hGdMGhi eMce dJMQjQ GdaJGhi s
(3BNQgG (B:s
(3hbO PcQg GdJfHjg ai GdhOjYI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hBdg hSde jJdhg cJGH GdEbQGQ s
(3PcQ ai GdNGJeI Cfg jJdhg cJGH GdEbQGQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JYdjb s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs